Information and communication technologies in the real kindergarten program - Tasic, Ivana S.; Raspopovic, Slađana M. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2023)
The development of information and communication technologies (ICT) and constant connection with the Internet, enables better performance of activities in preschool institutions, based on new educational interactive programs. The paper examines the way in which ICT as a means of educational work has positive effects on child development in the real kindergarten program. The authors of the paper searched the Internet for free resources, which can be used in the function of raising the quality of educational work. Using some of the found resources, the authors independently designed content for the development of concepts about insects and wild animals, which in their opinion, can be applied in a certain way, to improve and modernize practice in accordance with the principles of preschool education.